2020
DOI: 10.33314/jnhrc.v18i3.2816
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude about COVID 19 among Health Care Workers Working in Seti Provincial Hospital

Abstract: Background: Health care workers are at greater risk of infection during COVID 19 pandemic.  This study was carried out to assess the knowledge and attitude toward COVID-19 among healthcare workers at working at Seti Zonal Hospital. Methods: A cross-sectional study was performed between April and May 2020 at Seti Zonal Hospital with purposive sampling technique and self-administered questionnaire of the knowledge and attitude of healthcare workers regarding COVID-19. The demographic characteristics mean k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
3
8
0
1
Order By: Relevance
“…However, this study found that many international students had a positive attitude towards COVID-19 and that, despite the majority of them being religious, they also believed and perceived that COVID-19 was not a punishment from God, a clear contrast to other studies on pandemics like HIV/AIDs that found that many people regarded pandemics as signs of punishments from God due to the sins that people had committed, 9,30 and recent KAPs studies on COVID-19 in countries like Nepal and Hong Kong where they found low positive attitudes. 39,40 However, the results were in agreement with recent studies done Nigeria, China, and India where they also found that many people had a positive attitude towards COVID-19 and Cholera believed that they would fight and win anytime. 6,21,36 With regard to their views on safety, international students confidently indicated that they felt safe being in China despite the outbreak of COVID-19, which was also attributed to the measures that the authorities implemented to make sure foreigners living in China, including students, were guaranteed of their safety.…”
Section: Discussionsupporting
confidence: 90%
“…However, this study found that many international students had a positive attitude towards COVID-19 and that, despite the majority of them being religious, they also believed and perceived that COVID-19 was not a punishment from God, a clear contrast to other studies on pandemics like HIV/AIDs that found that many people regarded pandemics as signs of punishments from God due to the sins that people had committed, 9,30 and recent KAPs studies on COVID-19 in countries like Nepal and Hong Kong where they found low positive attitudes. 39,40 However, the results were in agreement with recent studies done Nigeria, China, and India where they also found that many people had a positive attitude towards COVID-19 and Cholera believed that they would fight and win anytime. 6,21,36 With regard to their views on safety, international students confidently indicated that they felt safe being in China despite the outbreak of COVID-19, which was also attributed to the measures that the authorities implemented to make sure foreigners living in China, including students, were guaranteed of their safety.…”
Section: Discussionsupporting
confidence: 90%
“…However, this study has few limitations. First, the sample size was moderate with the response rate of 40.8% which is comparable to the study done in an Italian teaching hospital where response rate was 25% [31] and a study done on emergency medical service worker where response rate was 68.8% [32] but less than 85% [33] and 92%, [34] which might be due to time constraints. Secondly, participants found the questionnaire very lengthy.…”
Section: )supporting
confidence: 49%
“…HCWs are at greater risk of infection during the COVID-19 pandemic [9] and are one of the first groups to receive vaccinations and to be involved in vaccination operation, so it is important to consider their attitudes about COVID-19 vaccination to better address barriers to widespread vaccination acceptance [10,11].…”
Section: Introductionmentioning
confidence: 99%